A Novel Microbiome Signature in Gastric Cancer: A Two Independent Cohort Retrospective Analysis. Issue 4 (13th October 2022) - Abate, Miseker; Vos, Elvira; Gonen, Mithat; Janjigian, Yelena Y.; Schattner, Mark; Laszkowska, Monika; Tang, Laura; Maron, Steven B.; Coit, Daniel G.; Vardhana, Santosh; Vanderbilt, Chad; Strong, Vivian E.
Abstract : Objective: The microbiome is hypothesized to have a significant impact on cancer development. In gastric cancer (GC), Helicobacter pylori is an established class I carcinogen. However, additional organisms in the intratumoral microbiome play an important role in GC pathogenesis and progression. In this study, we characterize the full spectrum of the microbes present within GC and identify distinctions among molecular subtypes. Methods: A microbiome bioinformatics pipeline that is generalizable across multiple next-generation sequencing platforms was developed. Microbial profiles for alpha diversity and enrichment were generated for 2 large, demographically distinct cohorts: (1) internal Memorial Sloan Kettering Cancer Center (MSKCC) and (2) The Cancer Genome Atlas (TCGA) cohorts. A total of 520 GC samples were compared with select tumor-adjacent nonmalignant samples. Microbiome differences among the GC molecular subtypes were identified. Results: Compared with nonmalignant samples, GC had significantly decreased microbial diversity in both MSKCC and TCGA cohorts ( P <0.05). Helicobacter, Lactobacillus, Streptococcus, Prevotella, and Bacteroides were significantly more enriched in GC samples when compared with nonmalignant tissue ( P <0.05). Microsatellite instability-high GC had distinct microbial enrichment compared with other GC molecular subtypes. Conclusion: Distinct patterns of microbial diversity and species enrichment were identified in patients with GC. Given the varied spectrum of disease progression and treatment response of GC, understanding unique microbial signatures will provide the landscape to explore key microbial targets for therapy.